Rancang Bangun Alat Pengering Biji Kopi Berbasis Internet Of Things - Asyiva Nurbaeti; Mila Kusumawardani; Hendro Darmono (Politeknik Negeri Malang, 2021)
This research propose to design a coffee bean dryer by utilizing a heater as a heating element to replace sunlight for the drying process of coffee beans. Ultrasonic sensor for detecting coffee beans in the dryer. When the temperature reaches 50°C, the heater, dimmer and fan will automatically turn off. All data will be processed using NodeMCU which will then be sent to the codular application. By utilizing IoT (Internet Of Things) technology, it is hoped that it can help smallholder coffee farming owners in monitoring and automatic drying of the coffee beans to be dried. From the test results, it can be concluded that the initial weight before curing is 250 grams, while the weight after curing is 247 grams. This is because there is a decrease in the water content in the coffee beans. The DHT22 sensor is able to measure an average temperature of around 49.75°C with an average humidity of 51.45% during the day, while for the night it is able to measure an average temperature of around 49.75°C with an average humidity of around 46.8%. The process of sending information from the device to Google Firebase via an internet connection, which takes an average of 0.01 seconds or 10 milliseconds, with this delay is included in the very good category.